ON THE USING OF THE «LABVIEW» IN EDUCATIONAL PHYSICAL WORKSHOP - Vitaly A. Orlov; Irina N. Orlova (Открытое образование (Москва))
The possibility of integrating the automation of measurements with real experimental in the training workshop is discussed. For an example of the laboratory workshop identifies the advantages and disadvantages of computer technology. It is proposed interpretation of the boundaries of virtualization of physical experiment, which begins to suffer for the quality of physics, as a researcher